A finite element analysis of the carpal arch with various locations of carpal tunnel release - Yu, Lu; Jia, Jingyi; Lakshminarayanan, Kishor; Li, Yiming; Gan, Yaokai; Yao, Yifei (Frontiers in Surgery, 2023)
Objective: The purpose of this study was to investigate the effects of TCL transection location on the biomechanical property of the carpal arch structure. It was hypothesized that carpal tunnel release would lead to increased carpal arch compliance (CAC) in a location-dependent manner. Methods: A pseudo-3-dimensional finite element model of the volar carpal arch at distal carpal tunnel was used to simulate arch area change under different intratunnel pressure (0-72 mmHg) after TCL transection at different locations along the transverse direction of TCL. Results: The CAC of the intact carpal arch was 0.092 mm2/mmHg, and the simulated transections ranging from 8 mm ulnarly to 8 mm radially from the center point of TCL led to increased CACs that were 2.6 - 3.7 times of the CAC of the intact carpal arch. The CACs after radial transections were greater than those ulnarly transected carpal arches. Conclusion: TCL transection in the radial region be biomechanically favorable in reducing carpal tunnel constraint for median nerve decompression.